Chapter Civilisation versus barbarie. L'Ennemi sous la plume des Léningradois assiégés - Gruszka, Sarah (Biblioteca di Studi Slavistici, 2017)
Leningrad under siege (1941-1944) appears to be a privileged context to study the perception of the Enemy by the Soviet people. The diaries kept by hundreds of exhausted and starved Leningraders allow an in-depth study of the terminology used by ordinary citizens to name the Germans (between fascism and internationalism) who bombed the city almost daily. It refines our understanding of the effectiveness of the Soviet propaganda, and thus contributes to a broader reflection on the mechanisms of internalization and deconstruction of the official discourse, and its influence on the popular language.